(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This paper examines the oldest parchments of the Putignani Fund (1303-1429) of the National Library «Sagarriga Visconti Volpi» of Bari purchased in 1914, which consists of several hundred membranous pieces, for a period of time between 1303 and 1742. The documentary corpus is not very uniform in terms of content and is quite varied by type, including public and private documents of various origins. For this last typology, also considering the mediocre state of conservation, accurate regests are provided with historical and prosopographical notes. These are deeds of sale, exchanges and ratifications, mainly concerning the city of Tricarico (Matera): one of these, in particular, adds new pieces regarding the relationship between the city itself and Barletta, whose stories are intertwined during the 14th century through the countess Sveva de Bessano. Three other notary documents concern the built-up area of Anzi, near Potenza. Of four membranes, related to litterae named after the kings Ladislaus and Joanna II and her husband Giacomo della Marca, included between 1408 and 1416 and concerning concessions, immunities and graces issued by the Angevin rulers in favor of Tricarico, it is also given in appendix the critical edition.